How to research multiple migrants? Introducing web-based respondent-driven sampling survey - Justyna Salamońska; Olga Czeranowska (University of Warsaw, Centre of Migration Research (CMR), 2018)
Multiple migrant populations are an under-researched group, perhaps because they pose particular challenges for survey research. First, they represent what literature refers to as a hard-to-survey population (Tourangeau 2014). Second, multiple migrations require taking into account multiple spatialities and hence highlight the potential of multi-sited research (originally developed within ethnographic studies). This working paper outlines some of the challenges related to quantitative research of multiple migrations that span multiple locations. Web-based Respondent-Driven Sampling (Web-based RDS) is presented as one solution to researching hidden populations of multiple migrants based worldwide, for which sampling frames are not available. RDS was initially designed for studying hidden populations (Heckathorn 1997). Web-based RDS is a version of the RDS carried out online. As in traditional RDS, in Web-based RDS, recruitment of respondents relies on migrant networks and utilises a dual incentive system. The online survey mode allows relative ease and low cost in reaching respondents based in various locations.
Keywords: 330; hard-to-survey population; multiple migrations; multi-sited research; Respondent-Driven Sampling; Web-based Respondent-Driven Sampling